2019
DOI: 10.5194/aab-62-335-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different floor materials on the welfare and behaviour of slow- and fast-growing broilers

Abstract: Litter quality and fast growth rate are the two main issues in broiler welfare. This study aimed to evaluate the effects of genotype and floor material on broiler welfare and behaviour. In the study, slow-growing (Hubbard JA57) and fast-growing (Ross 308) broilers on a slatted floor and deep litter were used; there were four main groups (2 genotype × 2 housing) and each treatment group consisted of 5 replicates. Each replicate group consisted of 10 male chicks, and 200 birds were used in total. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
5
28
1
Order By: Relevance
“…From day 14, foot pad health status for animals kept on the partially perforated flooring system was higher compared to those kept on litter at each day of life. This result is in line with several studies which have also observed a higher foot pad health status for animals kept on perforated flooring systems compared to litter flooring ( Cengiz et al., 2013 , Çavuşoğlu et al., 2018 , Çavuşoğlu and Petek, 2019 ). In addition, Tahamtani et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…From day 14, foot pad health status for animals kept on the partially perforated flooring system was higher compared to those kept on litter at each day of life. This result is in line with several studies which have also observed a higher foot pad health status for animals kept on perforated flooring systems compared to litter flooring ( Cengiz et al., 2013 , Çavuşoğlu et al., 2018 , Çavuşoğlu and Petek, 2019 ). In addition, Tahamtani et al.…”
Section: Discussionsupporting
confidence: 91%
“…Results for hock burn showed a higher hock health for animals kept on the partially perforated flooring system compared to litter flooring toward the end of the fattening period. Similar results regarding hock health were observed in several studies, all showing a higher hock health for animals kept on a perforated compared to a littered flooring system ( Almeida et al., 2017 , Çavuşoğlu et al., 2018 , Çavuşoğlu and Petek, 2019 ). In addition, Li et al.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Locomotor problems in broilers are often correlated with litter quality [84][85][86][87][88][89][90], since the ammonia excreted by the animals can provoke lesions in their feet. Additionally, they can be consequence of the high growth rate of animals [91][92][93][94] and of the increasing genetic selection for heavier major pectoralis muscle [56,65,95]. Clark et al [96] proposed that leg problems are an animal welfare issue as a result of animals being pushed beyond their physiological limits.…”
Section: Discussionmentioning
confidence: 99%